Nursing care for orthopedical patients in a public hospital in west Pará (Research, Society and Development, 2021)
The Patient Classification System characterizes the patient's need and degree of dependence on the care of the team, being the tool that helps in the systematization of care, contributing to the development of individualized and comprehensive care. Thus, the study aimed to investigate the role of nurses according to the degree of dependence of the patient victim of orthopedic trauma. This is a descriptive, cross-sectional, and qualitative study, with 4 nurses participating. Qualitative data were treated using the IRAMUTEQ software (R Interface for Multidimensional Text Analysis and Questionnaires). The text corpus gave rise to six thematic classes, which were grouped and titled according to their approach, supporting the construction of four categories of analysis: the view and practice of nurses in the face of the patient classification system, the practice of nurses in front of to staff dimensioning, the reflection of the reduced number of professionals in care and guidance directed to the patient at hospital discharge.